2005
DOI: 10.1227/01.neu.0000149008.73513.44
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Window of Vulnerability to Repetitive Experimental Concussive Brain Injury

Abstract: These data suggest that a single concussion is associated with behavioral dysfunction and subcellular alterations that may contribute to a transiently vulnerable state during which a second concussion within 3 to 5 days can lead to exacerbated and more prolonged axonal damage and greater behavioral dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
224
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(243 citation statements)
references
References 59 publications
17
224
2
Order By: Relevance
“…Therefore, as previously reported, 26,27 the present research offers a real time course of NAA, Cr, and Cho following mTBI, demonstrating transient cerebral hypometabolism (decrease in NAA and Cr) corresponding to the window of metabolic brain vulnerability. [1][2][3][5][6][7][8]10,11,35 In light of the data questioning the validity of neuropsychological tests to determine the safe return of athletes to play, 48,49 the present results, besides confirming that recovery of brain metabolism occurs much later than disappearance of postconcussive symptoms, once again indicate that 1 H MRS is a potent, unique tool with which to monitor the closure of the window of metabolic brain vulnerability following mTBI that may involve important brain metabolites such as NAA and Cr. Furthermore, the very recent report carried out in a cohort of 24 symptomfree athletes with concussive head injury (as assessed by clinical self-reported symptom resolution, cognitive and clinical balance testing (SCAT2 and Balance Error Scoring System), and clearance from a medical professional for the first stage of aerobic activity) showing significant alterations in brain metabolism (decrease in NAA in the genu but not in the splenium of the corpus callosum) strongly support the concept that clinical resolution is not coincident with normalization of brain metabolism.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, as previously reported, 26,27 the present research offers a real time course of NAA, Cr, and Cho following mTBI, demonstrating transient cerebral hypometabolism (decrease in NAA and Cr) corresponding to the window of metabolic brain vulnerability. [1][2][3][5][6][7][8]10,11,35 In light of the data questioning the validity of neuropsychological tests to determine the safe return of athletes to play, 48,49 the present results, besides confirming that recovery of brain metabolism occurs much later than disappearance of postconcussive symptoms, once again indicate that 1 H MRS is a potent, unique tool with which to monitor the closure of the window of metabolic brain vulnerability following mTBI that may involve important brain metabolites such as NAA and Cr. Furthermore, the very recent report carried out in a cohort of 24 symptomfree athletes with concussive head injury (as assessed by clinical self-reported symptom resolution, cognitive and clinical balance testing (SCAT2 and Balance Error Scoring System), and clearance from a medical professional for the first stage of aerobic activity) showing significant alterations in brain metabolism (decrease in NAA in the genu but not in the splenium of the corpus callosum) strongly support the concept that clinical resolution is not coincident with normalization of brain metabolism.…”
Section: Discussionsupporting
confidence: 61%
“…31,32 To explain their results, these authors concluded that an increase in total Cr (Cr and CrP) levels in the white matter may support a larger pool of high-energy phosphates (CrP and ATP), helping to restore mTBI-induced alteration of cell homeostasis through upregulation of membrane pumps and other processes of cellular repair. 28,29 Notwithstanding, these conclusions are in contrast with the notion of brain vulnerability, [1][2][3][5][6][7][8]10,11,35 which is characterized by a period of metabolic depression (hypometabolism), mainly due to mitochondrial malfunctioning, [36][37][38] particularly affecting NAA homeostasis 39 and ATP supply, [8][9][10][11]31,39 and also causing significant depletion in the total Cr pool. 31,32 Furthermore, given the relative CrP/ATP ratio in the brain tissue, ranging from about 0.8 (from Bryant et al) 32 to about 0.33 (from Signoretti et al), 31 it seems implausible that CrP may efficiently buffer ATP stores in the case of impaired ATP homeostasis.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, our interinjury interval was 48 h, which is similar to our previous work,13, 19 a temporal window during which the mouse brain is known to be vulnerable to subsequent injuries21 in order to mimic human situations (combat or sports) in which additional injuries are sustained prior to full recovery from the previous injury. At the end of the procedure, each animal was removed from the stereotaxic table and allowed to recover on a heating pad and, upon becoming ambulatory, was returned to its home cage.…”
Section: Methodsmentioning
confidence: 87%
“…Moreover, confirmation of the likely residual pathology from concussion is clearly demonstrated in the secondinjury circumstance, where a prior concussion increases the likelihood of a second concussion and greater morbidity of the second concussion in both human and animal studies (Huh et al, 2007;Longhi et al, 2005;Manville et Wall et al, 2006). The most straight forward explanation of the pathology of the second injury concussion is that the first concussion is simply not benign, but that the brain adapts quickly to the injury in most cases.…”
Section: Pathophysiology Of Concussionmentioning
confidence: 96%